Moraine chronology and deglaciation of the northern Lyngen Peninsula, Troms, Norway - Greig, David (Universitetet i Tromsø, 2011)
The northern Lyngen Peninsula in Troms, northern Norway, displays a suite of glacial and periglacial landforms that describe both a complex interaction of geomorphological processes and its history of deglaciation during the Late Weichselian and Holocene. These features include: cirque and valley glacier moraines, relict ice-cored moraines, rock avalanches, rock glaciers, a protalus rampart, and other talus-derived landforms. Morphological relationships of landforms within the three valleys of Strupskardet, Veidalen and Reindalen were studied in detail; using a combination of geographic information systems (GIS), aerial photograph interpretation, and field research. Seven distinctive glacial stages (comprised of up to 13 minor phases) were identified, and presented as a series of maps that describe the chronology of deglaciation within the study area. Relative-age dating of moraines was performed with a Schmidt hammer, which measured the rebound value (R-value) from boulder surfaces. This technique was found to be an effective tool that offered additional insight into the age of moraines and other landforms. Equilibrium line altitudes (ELA) were also calculated for reconstructed ice limits to elucidate the effects of local topography and regional climatic conditions on glacier formation.